Longitudinal associations of parent-child communication, dating behaviors, decision-making processes, and sex initiation among United States Latina/o adolescents - Cabral, Patricia; Wallander, Jan L.; Elliott, Marc N.; Schuster, Mark A. (Frontiers in Psychology, 2022)
Objective: To examine generational status differences in the longitudinal associations among early parent-child sex communication, dating behaviors, and sex initiation five years later, as mediated by perceived peer norms and attitudes among Latina/o adolescents. Methods: Using prospective longitudinal data from the Healthy Passages project, Latina/o girls (n = 879) and boys (n = 885) who were identified as 1st- (18%), 2nd- (58%), or 3rd- (24%) immigrant generational status reported on their dating behaviors and parent-child communication about sex at 5th grade (M age = 11.12), their perceived peer norms and attitudes regarding sex at 7th grade (M age = 13.11), and if they had initiated oral, vaginal, or anal sexual intercourse by 10th grade (M age = 16.06). Results: Third-generation Latina girls were more likely than 1st- and 2nd-generation Latinas to have initiated sexual intercourse by 10th grade. More advanced dating behaviors in 5th grade had a positive association with sex initiation for all generational status groups among Latino boys, but only among 1st-generation Latina girls. Moreover, mediating decision-making processes of peer norms and attitudes differed for each group. Conclusions: Pre-adolescent dating behaviors is associated with long-term differences in adolescents’ sexual behaviors, which may point to targets for prevention efforts. Acculturation differences may contribute to different ways in which adolescents decide to engage in sexual intercourse based on previous dating experience.